1997
DOI: 10.1177/036354659702500122
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of Arthroscopically Tied Knots

Abstract: It has been postulated that some arthroscopic shoulder stabilization failures may be due to knot slippage. In an effort to improve arthroscopic technique, we performed tensile testing on four arthroscopically tied knots with two commonly used suture materials. Handtied square knots served as controls. Sutures of No. 1 Maxon and No. 1 Ticron were used. Four types of sliding knot configurations were tested: the overhand loop, the Duncan loop, the Roeder knot, and the Snyder knot. Knots were tied via a knot pushe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
8

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 21 publications
4
77
0
8
Order By: Relevance
“…1). The biomechanical testing model was adapted from the technique of Mishra et al [11] which included a pre-load phase, a cyclical loading phase, and an ultimate (failure) loading phase. All knots were first preloaded to 5 N to remove the slack and the loop length was recorded to calculate loop security.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The biomechanical testing model was adapted from the technique of Mishra et al [11] which included a pre-load phase, a cyclical loading phase, and an ultimate (failure) loading phase. All knots were first preloaded to 5 N to remove the slack and the loop length was recorded to calculate loop security.…”
Section: Methodsmentioning
confidence: 99%
“…The studies of Loutzenheiser et al and Mishra et al [11,13,14] were the first studies published that compared the biomechanical attributes of different arthroscopic knot configurations. Currently, the study that has compared the most number of knots head-tohead examined ten knots [4].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have examined the biomechanical properties of arthroscopic knots, 4,10,12,13,15,18 but no study has evaluated the ease of learning and tying them. This study revealed that the Tennessee slider, Duncan loop, Revo knot, and Nicky's knot were the easiest for the surgeons in training to learn and use.…”
Section: Discussionmentioning
confidence: 99%
“…These relatively large suture sizes are commonly used in various procedures in the repair of the shoulder. 3 A tied suture has three components. The loop created by the knot maintains the apposition of tissue.…”
Section: Surgical Suturesmentioning
confidence: 99%